Embodiment and Psychological Health in Adolescence. 2. Embodiment Profiles and their Association with Psychological Health Among Young Adolescents - Lars-Gunnar Lundh; Lo Foster; Daiva Daukantaité (Journal for Person-Oriented Research)
Background. Several researchers have argued that disturbances in embodiment play an important role in the development of psychological health problems among adolescents. The purpose of the present study was to use the 12-item Embodiment Scale (ES-12), with its three subscales Harmonious Body (HB), Disharmonious Body (DB), and Body for Others (BO), (1) to identify subgroups of adolescents with different profiles on the ES-12 scales, and (2) to see how these profiles are associated with patterns of psychological health problems.